State failure: A public choice theory approach - García Sandoval, Carlos (2014)
The problem of state failure has become a recurrent phenomenon in much of the world and particularly in Latin America. The failures involve situations ranging from the implementation of populist policies, bureaucratization of governments, saturation of the supply of public goods, recurrent tendency to tax evasion, legal and political favoritism directed at pressure groups and corruption (of officials and politicians), among others. The alternative solutions have always revolved around the search for politicians and bureaucrats with leadership capacity and supposedly incorruptible, but in practice, this effort is not usually effective according to voters' expectations, because the failures of the State, although they can be minimized, never disappear. It can be said, then, that the failures of the State (whether in a democratic or totalitarian framework) are intrinsic to it because the conduct of the interacting agents in the realm of power responds to a certain rationality that is not concurrent with the objectives of others. The effect will be an imperfect state that will require the right incentives if these flaws are to be at least minimized.